ADVOCATE PROFESSION TOWARDS AUTOMATION IN INDUSTRIAL REVOLUTION 4.0 ERA - Kusumawardani, Qur'ani Dewi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
Legal service and business competition have changed in the last decade because of technology changes. Artificial Intelligence technology in the form of robots, chat bots, and digital assistants will influence the practice of law in industrial revolution 4.0 era. By 2025, based on The Learning Generation report, released by the United Nation Commissions on Financing Global Opportunity, said that half of the world’s jobs are at high risk to get the impact of automation in the coming decades. Legal profession such as lawyer will feel this impact, with the emergence of robot lawyers. The method used in this paper is a juridical normative method with statute approach and conceptual approach, and descriptive analysis. The results will be obtained from this study; firstly, correlation between advocate profession and automation. Secondly, law field which will get impact from automation. Thirdly, what the lawyer should prepare to face the condition of radical technology changing in Industry 4.0, because in this Era, we must innovate more rather just imitate past glory.